Antibacterial Activity of Garlic Extract Against some Pathogenic Animal Bacteria - M Safithri; M Bintang; M Poeloengan (Media Peternakan, 2011)
The antimicrobial activity of garlic extract against Gram-positive and Gram-negative bacterial isolates was well studied. However, reports on antibacterial activity of garlic extract against some pathogenic bacteria in animals in Indonesia, are still limited. Therefore, the aim of this study was to evaluate the antibacterial activity of water and ethanol extracts of garlic against Salmonella typhimurium in chickens, and Streptococcus agalactie, Escherichia coli, and Staphylococcus aureus causing mastitis in dairy cows in Indonesia. A filtrate of fresh garlic was used to determine the antibacterial activity against S. typhimurium at concentrations of 5%, 10%, 20%, 30%, and 40% w/v, whereas, the antibacterial activity of water and ethanol extracts was determined against S. agalactie, E. coli, and S. aureus at concentrations of 5%, 10%, 15%, 20%, and 25% w/v. Results showed that antibacterial activity of 30% garlic filtrate was equivalent to 10% tetracycline. Meanwhile, antibacterial activity of garlic aqueous extract on mastitis bacteria was better than that of the garlic ethanol extract. Aqueous extract of garlic at 20% had the same antibacterial activity as 0.01% ampicillin on mastitis bacteria. Filtrates of fresh garlic can be used to inhibit growth of S. typhimurium and mastitis bacteria.